Investing the role of arsenic trioxide on the expression of survivin splice variants and their specific microRNA during cell cycle progression and apoptosis in breast cancer MCF-7 cell line - Kagiso, Laka (My University, 2019)
Survivin is the smallest and a well-studied member of the inhibitors of apoptosis proteins (IAPs) family, which is involved in the regulation of cell division, inhibition of both caspasedependent and -independent apoptosis in cancer cells and promotion of angiogenesis. Survivin is detectable during embryonic and foetal development but is undetectable in normal adult tissues. It is, however, expressed in transformed cell lines as well as in most common types of human cancers. Regulation of survivin remains poorly understood, and the discovery of the regulatory biomolecules, microRNAs (MiRs) present an interesting opportunity to investigate the regulation of this protein and its variants in cancers, especially breast cancer. Additionally, the expression of the survivin splice variants during cell cycle progression and apoptosis is not fully understood. The aims of this study were to investigate the role of arsenic trioxide on the expression of survivin splice variants and their specific microRNAs during cell cycle progression and apoptosis in human breast cancer MCF-7 cells. The study also aimed at ascertaining the toxicity and efficacy of using coal fly ash-derived β-cyclodextrin carbon nanospheres to deliver arsenic trioxide into the MCF-7 cells. Carbon nanospheres (CNSs) were synthesised using a chemical vapour deposition method while arsenic trioxide was deposited using wet impregnation method to form the arsenic trioxide-β-cyclodextrin carbon nanospheres (ATO-β-cyclodextrin-CNSs). The formation of the CNSs and the loading of arsenic trioxide to CNSs were confirmed using scanning electron microscopy/energy dispersive X-ray detection (SEM-EDX). The in vitro cytotoxicity effect of the β-cyclodextrin carbon nanospheres (CNSs), arsenic trioxide and arsenic trioxide-β-cyclodextrin CNSs against KMST-6 and MCF-7 cells was analysed using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5 diphenyltetrazolium bromide (MTT) Assay, Muse® Count and Viability Assay and light/fluorescence microscopy. Cellular apoptosis, cell cycle analysis, Multi-Caspase activation, mitochondrial membrane potential, MAPK activation and PI3K activation were analysed using the Muse® Cell Analyser. Polymerase Chain Reaction (PCR) and Immunohistochemistry were used to analyse survivin mRNA variants and protein expression, respectively. The survivin specific MiRs were predicted using both bioinformatics platforms and literature surveys. In order to understand the applicability of delivering arsenic trioxide for the treatment of breast cancer, skin fibroblast (KMST-6) and MCF-7 cells were exposed to β-cyclodextrin CNSs. The novel β-cyclodextrin CNSs did not show any cytotoxic effect on the KMST-6 cells but demonstrated such activity against the MCF-7 cells. More so, arsenic trioxide-βcyclodextrin CNSs were found to significantly reduce the viability of the MCF-7 cells and were shown to inhibit their cell growth through the induction of apoptosis. The MTT Assay results revealed arsenic trioxide inhibited the growth of the MCF-7 cells in a concentration-dependent manner. The Muse® Cell Analyser showed that arsenic trioxide induced G2/M cell cycle arrest and promoted cellular apoptosis without any damage to the mitochondrial membrane of MCF-7 cells. Furthermore, arsenic trioxide also deactivated two survival pathways, Mitogen-Activated Protein Kinase (MAPK) and Phosphoinositide 3-Kinase (PI3K) signalling pathways in MCF-7 cells. The deactivation of the two pathways was shown to be accompanied by the upregulation of survivin 3α during arsenic trioxide-induced G2/M cell cycle arrest and apoptosis. Survivin 2B was found to be upregulated only during arsenic trioxide-induced G2/M cell cycle arrest, but downregulated during arsenic trioxide-induced apoptosis. However, wild-type survivin was highly expressed in untreated MCF-7 cells, but the expression was upregulated during arsenic trioxide-induced G2/M cell cycle arrest and was downregulated during arsenic trioxide-induced apoptosis. Survivin variant ΔEx3 was undetected in both untreated and treated MCF-7 cells. Survivin 2α was upregulated during arsenic trioxideinduced apoptosis whereas, survivin 3B was only detected in the untreated MCF-7 cells. Additionally, survivin proteins were localised in both the nuclei and cytoplasm in MCF-7 cells and highly upregulated during arsenic trioxide-induced G2/M cell cycle arrest, which can be attributed to the upregulation of survivin-2B. Using TargetScan, MIRD and mirTarbase, a few MiRs were identified and confirmed to target wild-type survivin, survivin 2B and survivin ΔEx3. These include the MiR-542-3p and MiR-335-5p, which are both upregulated during apoptosis and MiR-218-5p, which is upregulated during cell arrest. MiR-218-5p targets survivin 2B, which was upregulated during G2M cell cycle arrest. The fly ash-derived CNSs can be used to deliver arsenic trioxide for therapeutic purposes, especially against breast cancer. Most importantly, these nanoparticles induced typical apoptotic characteristics in breast cancer MCF-7 cells. Arsenic trioxide can be used as therapeutic target for breast cancer treatment and nanotechnology can be used for its delivery. This study provided the first evidence that novel survivin 2B splice variant may be involved in the regulation of arsenic trioxide-induced G2/M cell cycle arrest only. This splice variant can therefore, be targeted for therapeutic purposes against Luminal A breast cancer cells
Thesis (M.Sc. (Biochemistry)) -- University of Limpopo, 2019
Keywords: Survivin; Arsenic trioxide; Apoptosis protein; Breast cancer; Arsenic trioxide; Apoptosis; Breast cancer